(untitled) (South East Asia Journal of Public Health, 2013)
The aim of the study is to assess the magnitude of the problem and certain epidemiological factors associated with malaria and examine the changing pattern of malaria through its parameters of measurement during 2009-2011. The study was carried out at the Rural Health Training Center (RHTC), under the J. N. Medical College, Aligarh Mus-lim University, Aligarh, (India) for three years from 1st January 2009 to 31st December 2011. Teams of doctors and paramedical staff regularly visited the villages. If any person was found to be suffering from fever, his/her blood was examined for the malaria parasite. Patients were given presumptive treatment and radical treatment if slides were positive. The findings of the study demonstrated that the number of malaria cases increased during the study period, but in the year 2010, a sudden upsurge was noticed. Out of 5594 patients, most of the patients seen were in the age group of 11-20 years (34.3%). P. vivax (96.2%) was the most common malaria infection in these areas. An increasing trend of malaria was seen from July to October. Most of the parameters of malaria measurement in-creased many folds in 2010 and showed a declining trend in 2011. The overall findings of the study indicated the high endemicity of malaria in the study area and demonstrated a changing pattern of malaria in the registered vil-lages as most of the parameters of malaria measurement increased. An integrated approach is needed which in-cludes mass survey or active surveillance, and appropriate drug therapy to tackle this public health problem. DOI: http://dx.doi.org/10.3329/seajph.v2i2.15940 South East Asia J Public Health | Jul-Dec 2012 | Vol 2 Issue 2 | 28-33